Style and Genre Aspects of Kazym Khanty Bear Festival Songs: (Based on the Materials of the Author's Research in 1988–1997). Issue 1 (2nd January 2016) - Vasylenko, Ol'ha V.
Abstract : The bear festival of the Kazym Khanty represents a multicomponent cultural and religious phenomenon, featuring key ritual and mythic symbols of the Khanty world, closely correlated to the richest level of Ob'-Ugrian musical depth. Relevant literature encompasses significant works by ethnographers, musicologists, and culturologists from the eighteenth through nineteenth centuries. Nevertheless, the style and genre aspects of analyzing ritual bear-honoring songs of the Kazym Khanty has been insufficiently studied. The article explores the genre and musical component of the bear festival as a unified traditional culture conceptual text. Classification of the ritual songs requires studying the rite's dramaturgy, integrated structurally. The ritual bear complex and its actions can be structurally analyzed according to genre and by ethnic group. Theoretical interpretation and musical style typology can be derived using a hierarchy of Kazym Khanty bear songs. Aleatoric principles [from Latin, aleatorius or playful] pertain to songs within a genre group in a specific order, as in the preliminary moments of a shamanic séance, thus indicating the musical structure of the bear festival in each concrete situation. Homogeneity characterizes melodies that are sacral and profane. The entire rite forms a stylistic series: sequential (a horizontal axis, within phrases, genre groups and songs), and diachronic (a multi-temporal vertical axis). Intonation enables a unified environment that integrates song arrangement. The bear festival is therefore envisioned as a style and genre system.